2022
DOI: 10.1111/andr.13266
|View full text |Cite
|
Sign up to set email alerts
|

Chicken ovalbumin upstream promoter transcription factor type II interacts and functionally cooperates with GATA4 to regulate anti‐Müllerian hormone receptor type 2 transcription in mouse MA‐10 Leydig cells

Abstract: Background: Leydig cells produce testosterone and insulin-like 3, two hormones essential for male sex differentiation and reproductive function. The orphan nuclear receptor, chicken ovalbumin upstream promoter transcription factor type II (COUP-TFII), and the zinc finger factor GATA4 are two transcription factors involved in Leydig cell differentiation, gene expression, and function. Objectives: Several Leydig cell gene promoters contain binding motifs for both GATA factors and nuclear receptors. The goal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…NR2F2 regulates the transition from the adult progenitor Leydig cell (characterized by their elongated shape, their ability to proliferate and a low level of testosterone synthesis) to the immature ALC (characterized by their round shape, low mitotic activity and increased testosterone production) (50,63). In agreement with its in vivo role promoting maturation along the ALC lineage, NR2F2 co-operates with NR5A1 and GATA4 to activate the transcription of Insl3, Star (encoding the cholesterol transporter) and Amhr2 (46,(67)(68)(69)(70) in MA-10 cells, an in vitro model for immature ALC. Here we found that the steroidogenic cells that differentiate in Nr2f2 mutant fetal testes exhibit a small size, an elongated shape and reduced steroidogenic gene expression, features of the earliest stages of FLC differentiation (19,48,63).…”
Section: Discussionmentioning
confidence: 86%
“…NR2F2 regulates the transition from the adult progenitor Leydig cell (characterized by their elongated shape, their ability to proliferate and a low level of testosterone synthesis) to the immature ALC (characterized by their round shape, low mitotic activity and increased testosterone production) (50,63). In agreement with its in vivo role promoting maturation along the ALC lineage, NR2F2 co-operates with NR5A1 and GATA4 to activate the transcription of Insl3, Star (encoding the cholesterol transporter) and Amhr2 (46,(67)(68)(69)(70) in MA-10 cells, an in vitro model for immature ALC. Here we found that the steroidogenic cells that differentiate in Nr2f2 mutant fetal testes exhibit a small size, an elongated shape and reduced steroidogenic gene expression, features of the earliest stages of FLC differentiation (19,48,63).…”
Section: Discussionmentioning
confidence: 86%